Institutional Integration in the Sphere of Business Infrastructure in the European Union in the Years 2000-2008 - Balcerzak, Adam P. (Journal of Reviews on Global Economics, 2013)
Abstract: The last decade has been a period of accelerated integration in Europe. A manifestation of this was the biggest ever enlargement of the EU in 2004. Therefore the aim of this study is an evaluation of integration process in EU in the sphere of economic institutional order. The analysis concentrates on the institutional factors that affects the ability of country to utilize potential of competitive global economy. In this study some taxonomic tools were used - a hierarchical classification procedure (Ward's method with Euclidean and Manhattan distance). The study was based on annual data from the period 2000-2008. It allowed to capture a period of four years before and after the biggest enlargement of the EU. The research problem of this study amounted to the question: whether in the analyzed period can one speak about the process of growing similarities in the sphere of business institutional order for â€œoldâ€ and â€œnewâ€ EU countries? The study confirms existence of integration processes in relation to institutional order. However, it also proves the existence of group of countries that can be described by homogenous institutional factors especially effective in supporting utilization of the potential of competitive global economy.